Pemantauan Progres Luka pasca-Debridement Ulkus Diabetikum Menggunakan Bates-Jensen Wound Assessment Tool (BWAT): Laporan Kasus - Muftadi Adi; Siska Mariana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Background: Diabetic ulcer is a chronic complication of diabetes mellitus that may lead to amputation if not managed properly. The wound healing process requires objective monitoring, one of which is the Bates-Jensen Wound Assessment Tool (BWAT) which assesses 13 wound aspects. Objective: To report the application of BWAT in monitoring wound healing post-debridement in patients with diabetic ulcers. Method: A case report involving two patients with diabetic ulcers treated at Teluk Pucung District General Hospital (Class D). Monitoring was conducted for three consecutive days using BWAT. Data were collected through direct observation, interviews, physical examinations, laboratory tests, and medical records. Results: The first subject (Mrs. M) showed a decrease in BWAT score from 30 to 24 within three days, indicating wound healing progress through reduced necrotic tissue, increased granulation, and epithelialization. The second subject (Mr. T) remained high (53 to 50), reflecting slow wound healing due to poor glycemic control, infection, and diabetic nephropathy. Conclusion: BWAT is effective as an objective tool for monitoring wound conditions post-debridement in diabetic ulcers.